Acute decompensated heart failure as a reason of premature chemotherapy discontinuation may be independent of a lifetime doxorubicin dose in lymphoma patients with cardiovascular disorders. (15th May 2017) - Szmit, Sebastian; Jurczak, Wojciech; Zaucha, Jan Maciej; Długosz-Danecka, Monika; Sosnowska-Pasiarska, Barbara; Chmielowska, Ewa; Joks, Monika; Drozd-Sokołowska, Joanna; Knopińska-Posłuszny, Wanda; Spychałowicz, Wojciech; Kumiega, Beata; Charliński, Grzegorz; et al.
Abstract: Background: Algorithm of anthracycline-based chemotherapy with favourable cardio-oncological outcome should be clearly re-defined for lymphoma patients with significant pre-existing cardiovascular diseases. A clinical benefit of liposomal forms of anthracycline is still debatable. Methods: Polish registry included observations of 138 lymphoma patients with concomitant cardiovascular disorders who received liposomal doxorubicin as cardioprotective alternative of conventional form. It was created to analyse the importance of a strategy of administration of conventional/liposomal doxorubicin and a lifetime doxorubicin dose for development of acute decompensated heart failure (ADHF) as a reason of premature chemotherapy discontinuation. Results: ADHF was the cause of premature termination of chemotherapy only in 11 patients (7.97%). The five new episodes of ADHF related to liposomal doxorubicin were recorded in subgroup of 70 patients with pre-existing heart failure (7.14%). There was the similar incidence of ADHF when liposomal doxorubicin was applied after conventional form in dose 200 mg/m 2 or if earlier signs of iatrogenic myocardial damage was recognised: 5 cases in subgroup of 51 patients with baseline cardiovascular risk factors (9.8%). ADHF was observed in one of 17 patients (5.88%) receiving liposomal doxorubicin as second line chemotherapy after first line with conventional doxorubicin. Consequently throughout the study group ADHF didn't depend on the total cumulative dose of all types of doxorubicin: OR = 0.85; 95%CI: 0.66–1.10; p = 0.22 for each 50 mg/m 2 . Conclusion: The schedule of administration of conventional/liposomal doxorubicin can decide that lifetime combined doses of anthracyclines become insignificant for ADHF occurrence and premature discontinuation of chemotherapy in lymphoma patients with pre-existing cardiovascular disturbances.